Development of antimicrobial starch-based bioplastics using aromatic plants by-products - Cruz, João Filipe Silva (2021)
The excessive use of non-biodegradable single-use packaging and the limited recycling capacity of these materials result in the accumulation of large amounts of plastics in the environment, harming biodiversity in various ecosystems. To minimize this environmental issue, several biodegradable plastics have been developed, commonly called bioplastics. On the other hand, the packaging of food products with inert plastics, i.e., free of activity capable of promoting an increase in the shelf-life of foods, increases food waste. As an alternative, active materials have emerged, i.e., materials capable of interacting with the food or the atmosphere in which it is packaged, minimizing the occurrence of chemical reactions or the growth of microorganisms responsible for its deterioration. Active packaging is often developed either by using active polymers or by incorporating molecules capable of conferring functionality to inert materials, such as essential oils (EO). These compounds exist in natural matrices, such as aromatic plants. However, the economic/energy effort involved in their extraction, as well as the use of food products as sources of EO still compromise their use in the development of active bioplastics. In order to develop a sustainable strategy for the development of active bioplastics, in this work we studied the possibility of developing antimicrobial starch-based bioplastics by using the by-products of aromatic plants, namely dried stems and leaves of winter savory and lemongrass, often wasted in the industrial processing of aromatic plants. For this purpose, two approaches were followed: (1) extraction of EO from the by-products of winter savory and lemongrass for incorporation into a starch-based bioplastic formulation; (2) incorporation of the crushed and sieved by-products of winter savory and lemongrass into a starch based bioplastic formulation. In each of the approaches, the influences of EO or by-products on the moisture content, chromatic properties, wettability, mechanical properties and antimicrobial activity of the bioplastic formulation were evaluated. The incorporation of EO extracted from the by-products of winter savory or lemongrass slightly increased the moisture content of the bioplastic and didn’t significantly affect its chromatic, mechanical and wettability properties. Furthermore, EO inhibited the growth of Staphylococcus aureus when incorporated into the bioplastic. In turn, the incorporation of crushed winter savory by-products conferred a brown coloration to the bioplastic formulation, became them opaque, increased their moisture content and Young’s Modulus from 0.23 % and 53.8 MPa to 0.57 % and 92.6 MPa, respectively; and, decreased their hydrophobicity to 88 %. Regarding antimicrobial activity, this strategy showed higher efficacy in inhibiting the growth of S. aureus (85 %) than EO incorporation (37 %). This profile was similar for the bioplastic formulation/crushed lemongrass by-products, except for the antimicrobial activity that was lower (53 %) than that observed in the bioplastic formulation/crushed winter savory by-products. In summary, the by-products of winter savory and lemongrass were shown to be sources of molecules suitable for the development of antimicrobial bioplastics, whose physicochemical, mechanical and biological properties can be manipulated by incorporating these by-products merely ground, not requiring costly processes for the extraction of the antimicrobial compounds. Therefore, winter savory and lemongrass by-products are potential candidates for the expansion of antimicrobial bioplastics in the packaging sector, a strategy that will not only decrease the environmental footprint of this sector, but also contribute to the valorization of aromatic plant by-products.